Cervical spondylotic myelopathy: surgical decision making - (:unkn) unknown (My University, 1996)
Cervical spondylotic myelopathy can produce a variety of clinical signs and symptoms secondary to neural compromise and biomechanical involvement of the spine. The surgical treatment of cervical spondylotic myelopathy remains a controversial issue after many years of study, evolution, and refinement. Several ventral, dorsal, or combined approaches have been defined. The complications associated with ventral approaches and the concerns about kyphosis following dorsal approaches led to the development of a variety of laminoplasty procedures. This paper reviews the biomechanical basis of cervical spondylotic myelopathy and its effect on choosing the appropriate surgical approach.